Synthesis and molecular characterization with DFT study of 2-chloro-1-(3-methyl-3-mesityl-cyclobutyl)-ethanone - Koparir, Pelin; Omar, Rebaz; Koparir, Metin (Natl Inst Science Communication & Policy Research-Niscpr, 2022)
In this study, we have presented the synthesis and structure analysis of 2-chloro-1-(3-methyl-3-mesityl-cyclobutyl)ethanone. The molecular elucidation is conducted by Fourier transform infrared (FT-IR) and Nuclear magnetic spectroscopy NMR (H-1 and C-13-NMR). The FT-IR recording in 4000-500 cm(-1) are done in KBr solid phase, while the NMR spectrum for both H-1 and C-13-NMR are done in the DMSO-6. Density functional theory (DFT) was used to stimulate and confirm the structure and molecular characteristics, using the DFT/B3LYP/cc-pVDZ method to study various conformers of the compound and their minimum energies by the scanning potential energy surface. In addition, the molecular electrostatic potential (MEP) map and charge spreading have been plotted for the molecule to account for the chemical reactivity and site selectivity. Furthermore, the thermodynamic properties for the molecule have been studied. A good correlation is found between experimental and simulation studies for FT-IR and NMR results. In the simulation data, the differences of energy between the conformers are found to be very small.
Keywords: Cyclobutane; DFT; MEP; Molecular reactivity; Thermodynamic properties